HUBUNGAN ETIKA DENGAN PROFESI DALAM BIDANG HUKUM DAN SIKAPNYA DI ERA GLOBALISASI - M. Muhyiddin Azzuhdi; Kiki Ardasiah; Ahmad Muadz Asmuni (JOURNAL SAINS STUDENT RESEARCH, 2024)
Professional ethics is an ethical attitude as an integral part of one's attitude towards living one's life as a professional. Only the professional in question himself can or knows best whether his behavior in carrying out his profession meets the ethical demands of his profession or not.The relationship between ethics and the legal profession, that professional ethics is an attitude to life, in the form of a willingness to provide professional services in the legal field to the community with full involvement and expertise as a service in order to carry out duties in the form of obligations to the community who need legal services accompanied by in-depth reflection.The types of work carried out by humans in ancient times and today are very different. The work of people in the past mostly only focused on energy or physical work, but in the current era of digitalization, human work is easier with the help of machines or robots and digital access.